2008
DOI: 10.1128/jvi.01605-08
|View full text |Cite
|
Sign up to set email alerts
|

The N-Terminal Region of an Entomopoxvirus Fusolin Is Essential for the Enhancement of Peroral Infection, whereas the C-Terminal Region Is Eliminated in Digestive Juice

Abstract: The spindles of Anomala cuprea entomopoxvirus (AncuEPV), which are composed of glycoprotein fusolin, are known to enhance the peroral infectivity of AncuEPV itself and of nucleopolyhedroviruses. This has been demonstrated to involve the disruption of intestinal peritrophic membrane (PM), composed of chitin matrix, glycosaminoglycans, and proteins. To identify essential and nonessential regions for this enhancement activity, AncuEPV fusolin and its deletion mutants were expressed in Sf21 cells using a baculovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…My group has identified the region of AcEPV fusolin, which is involved in the viral enhancing activity by assaying the activity of various AcEPV fusolin mutants using a bioassay system including BmNPV and B. mori larvae 22 . Namely, the N-terminal region (ca.…”
Section: Analyses Of Fusolinmentioning
confidence: 99%
See 4 more Smart Citations
“…My group has identified the region of AcEPV fusolin, which is involved in the viral enhancing activity by assaying the activity of various AcEPV fusolin mutants using a bioassay system including BmNPV and B. mori larvae 22 . Namely, the N-terminal region (ca.…”
Section: Analyses Of Fusolinmentioning
confidence: 99%
“…Furthermore, Hukuhara et al (2001) 9 expressed a PsEPV fusolin gene that had been introduced into E. coli, and it was found that the protein produced by this gene enhanced PuNPV infection in P. separata larvae by nearly 270-fold. My group has expressed the AcEPV fusolin gene in a baculovirus foreign gene expression system, and found that the resulting protein enhanced BmNPV infection of B. mori third-instar larvae by about 320-fold, but the degree of the enhancement appeared higher in the case of second instar larvae 22 . Furthermore, the enhancement of the infectivity of AcEPV by AcEPV fusolin produced by a baculovirus expression system was observed in A. cuprea larvae 22 .…”
Section: Developing Efficient Production-methods Of Fusolin For Its Pmentioning
confidence: 99%
See 3 more Smart Citations